152k views
0 votes
HELP ASAP PLEASE & SHOW UR WORK!! THANK YOU <333

Solve the following quadratic equation by using the quadratic formula.
-2x^2 - 3x + 4 = 0

User Tavnab
by
4.5k points

1 Answer

5 votes

Answer:


\bold{x_1=-(3+√(41))/(2)\approx-4.7\ ,\quad x_2=-(3-√(41))/(2)\approx1.7}

Explanation:


-2x^2-3x+4=0\\\\a=-2\,,\ b=-3\,,\ c=4\\\\\\x=(-b-√(b^2\pm4ac))/(2a)=(-(-3)\pm√((-3)^2-4(-2)(4)))/(2(-1))=(3\pm√(9+32))/(-2)\\\\\\x_1=-(3+√(41))/(2)\approx-4.7\ ,\qquad x_2=-(3-√(41))/(2)\approx1.7

User Brei
by
5.0k points